Relationship between Drugs, Diabetes Mellitus and Hypertension with Obesity in Sera of Women after Menopause - Abrahem, Suhad Abdlaziz (Al-Nahrain Journal of Science, 2013)
The Study aims to estimate serum levels of glucose, cholesterol, triglyceride and HDL in thirty postmenopausal who take Diabetes medicine only or with hypertension medicines. The study also includes twenty postmenopausal who not take any medicine as control group. Relationship of BMT, BSA, LBW and IBW was carried out with glucose and lipid profile in studied groups. Results showed that there were significant higher values of the LBW and IBW also there were significant increase in the level of cholesterol, LDL, VLDL and total lipidlevels with (P>0.01( in compared to control groups